Hibridación cultural a través de cortometrajes animados: estrategias narrativas y comunicación intercultural - Dr. Xin WANG (Fonseca, Journal of Communication, 2023)
The creation and dissemination of animated short films in the context of exchanges between the East and the West have their own characteristics, which reflect their national identities and cultural hybridization in globalization. Our research consists in selecting the most representative cases of animated short films originating from two important countries in East Asia, China and Japan in the 21st century, analysing and exploring intercultural communication and cultural hybridization through the process of storytelling, characterization, the construction of symbols and the metaphors of narratives.